Case report: Endoscopic closure with double stenting and autologous fascia lata graft of large tracheo-esophageal fistula - Mattioli, Francesco; Serafini, Edoardo; Andreani, Alessandro; Cappiello, Gaia; Marchioni, Daniele; Pinelli, Massimo; Tonelli, Roberto; Clini, Enrico; Marchioni, Alessandro (Frontiers in Surgery, 2023)
Introduction Radiotherapy and esophageal stenting are usually employed to manage esophageal localization of distant cancer. However, they are also related to the occurrence of an increased risk of tracheoesophageal fistula. Tracheoesophageal fistula management in these patients involves dealing with poor general conditions and short-term prognosis. This paper presents the first case in literature of bronchoscopic fistula closure through an autologous fascia lata graft placement between two stents. Case report and aim A 67-years-old male patient was diagnosed with pulmonary squamous cell carcinoma in the inferior lobe of the left lung with mediastinal lymph node metastasis. After a multidisciplinary discussion, bronchoscopic repair of tracheoesophageal fistula with autologous fascia lata was decided without the removal of the esophageal stent due to the high risk on the esophagus possibly related to such a procedure. Oral feeding was progressively introduced without the development of aspiration symptoms. Videofluoroscopy and esophagogastroduodenoscopy were performed at 7 months showing no signs of tracheoesophageal fistula patency. Conclusion This technique might represent a low risks viable option for patients unsuitable for open surgical approaches.